2016
DOI: 10.1002/2016jc011983
|View full text |Cite
|
Sign up to set email alerts
|

Physical drivers of chlorophyll variability in the open South China Sea

Abstract: The variability of chlorophyll a concentration (Chl a) in the open South China Sea (SCS) was examined using observations from two Bio‐Argo floats. During the period of September 2014 to August 2015, there was a permanent subsurface Chl a maximum (SCM) in the depth range of 48 to 96 m in the central basin of the SCS. In the northern basin, the SCM disappeared in winter, replaced by enhanced surface layer phytoplankton with high Chl a. The values of the SCM were influenced by the vertical displacement of isother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 73 publications
(201 reference statements)
2
42
0
Order By: Relevance
“…The continuous observations of the vertical variations provided by profiling floats allow us to build a 2‐D (depth‐time) view of upper‐ocean [Chla], b bp , FDOM, oxygen, as well as physical properties during the winter of 2014–2015. Float 0347 recorded concurrent MLD deepening from early October 2014 and an enhancement of surface [Chla] ([Chla] ML > 0.1 mg/m 3 , Figure c), consistent with studies based on remotely sensed satellite data (also see Zhang et al, ). This “surface bloom” attained its peak (maximal [Chla] ML reached 1.75 mg/m 3 , a 15‐fold increase in magnitude) in December, was sustained for about 2.5 months and was followed by a fast decay in February, with [Chla] ML attaining low values (< 0.1 mg/m 3 ) at the end of May.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The continuous observations of the vertical variations provided by profiling floats allow us to build a 2‐D (depth‐time) view of upper‐ocean [Chla], b bp , FDOM, oxygen, as well as physical properties during the winter of 2014–2015. Float 0347 recorded concurrent MLD deepening from early October 2014 and an enhancement of surface [Chla] ([Chla] ML > 0.1 mg/m 3 , Figure c), consistent with studies based on remotely sensed satellite data (also see Zhang et al, ). This “surface bloom” attained its peak (maximal [Chla] ML reached 1.75 mg/m 3 , a 15‐fold increase in magnitude) in December, was sustained for about 2.5 months and was followed by a fast decay in February, with [Chla] ML attaining low values (< 0.1 mg/m 3 ) at the end of May.…”
Section: Resultssupporting
confidence: 86%
“…Generally, in the northern SCS, the DCM appeared in spring after the MLD shoaling, deepened in summer with increasing solar illumination (PAR0), shoaled in the autumn, and disappeared in winter due to strong mixing (Zhang et al, ). This evolution is typical of oligotrophic regions such as the North Pacific subtropical gyre and Mediterranean Sea (Letelier et al, ; Mignot et al, ), with, however, shallower MLD in the SCS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the strength of winter monsoons and the cooling of surface temperature, the water column in the SCS and ECS was well-mixed, with the mixed-layer depth (MLD) deepening from summer to winter [40][41][42]. Liu et al (2002) observed a deeper subsurface Chl a maximum (SCM) at 75 m in September 1998 and a shallower SCM at 40~50 m at the same site in January 1999 in the Northern SCS [43].…”
Section: Seasonal Effectsmentioning
confidence: 99%